Effectiveness of Custom-Made Foot Orthoses vs. Heel-Lifts in Children with Calcaneal Apophysitis (Sever's Disease): A CONSORT-Compliant Randomized Trial - Javier Alfaro-Santafé; Antonio Gómez-Bernal; Carla Lanuza-Cerzócimo; José-Víctor; Aitor Pérez-Morcillo; Alejandro-Jesús A (MDPI AG, 2021)
The aim of the present research was to determine the effectiveness of relieving calcaneal apophysitis pain using "off-the-shelf" heel-lifts and custom-made orthotics. Two intervention modalities were evaluated and compared in a 12-week follow-up trial. Inclusion criteria included 9- to 12-year-old children diagnosed with calcaneal apophysitis. Children were randomly stratified into treatment A (custom-made polypropylene foot orthoses) and treatment B ("off-the-shelf" heel-lifts) groups. Treatment effectiveness was measured by algometry and the visual analogical scale (VAS). A total of 208 patients were included. The treatment A group showed an increase in threshold algometry of 53.4% (95% CI 47.1% to 59.7%) and a decrease in VAS of −68.6% (95% CI −74.5% to −62.7%) compared with the treatment B group (p < 0.001). Calcaneal apophysitis pain perception was improved in both groups, but children who used custom-made foot orthoses showed a greater improvement.